Australia under cyber attack : dissecting Canberra's response - Tan, Eugene E. Guang (2020)
Attributing cyber attacks to state-sponsored actors is a delicate balancing act that requires strategic and political thinking. States may or may not choose to name the offending state based on their own national interests. What is more important is how states should improve their capabilities to actively deter malicious actors.